(untitled) - Zill, Dennis G. (Victoria, Australia, 2005)
Differential equations with boundary-value problems with accompanying CD-ROM and technology! Straightfoward and readable, this mathematics text provides you with tools such as examples, explanations, definitions, and applications designed to help you succeed. The accompanying DE Tools CD-ROM makes helps you master difficult concepts through twenty-one demonstration tools such as Project Tools and Text Tools. Studying is made easy with iLrn® Tutorial, a text-specific, interactive tutorial software program that gives the practice you need to succeed.
Keywords: Boundary value problems,Differential equations; Textbooks,Textbooks